Ecological association of Pinus pseudostrobus (Pinaceae) in response to biogeographical variations in Central-Southern of Mexico - Sandoval-García, Rufino; González-Cubas, Rigoberto; Bautista-Cruz, Angelina (Instituto de Ecología, A.C., 2020)
Background and Aims: Pinus pseudostrobus is a species with a very wide geographical distribution range with climatic variations, a situation that has allowed it to be determined of great economic and ecological importance, so it is of much interest to know its natural association with other species to define management strategies and conservation. In this study, we analyze the patterns of ecological association and their correlation with biogeographic variables in the subprovinces of the Neovolcanic belt and the Sierra Madre del Sur. Methods: Geographical records of the genera associated with P. pseudostrobus were used to analyze spatial patterns through a multivariate statistical analysis and a species mix index. The ecological association of P. pseudostrobus was determined with 535 circular geospatial sites with a surface of 78.54 ha at a minimum distance of 1000 m. A scientific validation of all species was carried out to corroborate their coexistence in the regions of the present study. Key results: The subprovinces share 76% of the species associated with P. pseudostrobus, being the Sierra Madre del Sur which presented the greatest mix of species (Mi=0.45). The ecological association of P. pseudostrobus showed a relationship with 34 species in southern Mexico and 25 in the center, mainly from the genera Pinus, Quercus and Abies. Altitude and precipitation variables were significantly correlated as a predictor in the degree of association. Conclusions: The ecological association of P. pseudostrobus is similar in the subprovinces, but it differs in its dominance by the biogeographical variations. These results have implications for defining biodiversity management and conservation strategies, because in areas with high association the natural structure and composition must be maintained and in degraded areas functional groups must be contemplated.